Harmony of the foramen magnum and cranium: An anatomical and radiological study - Sema Özandaç Polat; Duygu Vurallı; Mahmut Oksüzler; Pınar Göker (Cukurova Medical Journal, 2022)
Purpose: The measurements’ reference points associated with foramen magnum (FM) and cranium were examined in this retrospective study. Also, the relation between FM and cranium harmony were calculated both on dry skull and in healthy subjects performed on computed tomography (CT). Materials and Methods: The present study was carried out on 185 healthy adult subjects (90 females; 95 males) aged between 18–67 years and 15 dried skull of unknown gender of an Anatolian population. The shapes of the FM were classified as two semicircle, oval, round, egg, tetragonal, pentagonal, hexagonal and irregular shapes. The anteroposterior length and transverse width of the FM and cranium were measured on both photos and CT. Results: The means and standard deviations of the measurements were given for three groups. To control the accuracy of FM width (FMW) and length (FML) results, a formula was used for three groups including dried skull and CT measurements of females and males, seperately (FMW=Cranial width (CW)/4.26 for group 1, CW/4.66 for group 2 and CW/4.66 for group 3; and FML=Cranial length (CL)/4.51 for group 1, CL/4.33 for group 2 and CL/4.16 for group 3). The oval type FM was predominant (26.67%) in dried skull and (23.33%) in females and (28.42%) in males. Conclusion: The present study presents noteworthy data about FM and cranium harmony of the adult Turkish population and dry skulls that will show a harmony between cranium and foramen magnum in clinical practice. There was no tetragonal and hexagonal FM types in dried skulls and tetragonal type FM was the least seen type in females and males.